PENDAMPINGAN PEMBUATAN TRAVELLING PAPER SOAP UNTUK MENINGKATKAN SANITASI ENDEMIK COVID-19 PADA MASYARAKAT DI DESA TANJUNG PERING SUMATERA SELATAN - Elsa Fitria Apriani; Dwi Hardestyariki; Adik Ahmadi; Viva Starlista (Jurnal Abdi Insani, 2023)
The decline in COVID-19 cases in Indonesia indicates that the pandemic status is starting to transition towards endemic. Endemic to COVID-19 does not mean that the COVID-19 virus has completely disappeared, so people still need to maintain a healthy lifestyle, one of which is maintaining sanitation. The use of soap is considered impractical so it is necessary to innovate sanitary products in the form of traveling paper soap in the form of paper soap which is easy to carry anywhere. The purpose of this service is to provide assistance in making mobile paper soap to improve sanitation endemic to COVID-19 and to help improve the skills and economy of the community in Tanjung Pering Village, South Sumatra. The community service method used in this activity is in the form of practice, counseling, technical guidance and assistance. The service was carried out in approximately 2 months for PKK mothers in Tanjung Pering Village, South Sumatra. Prior to the assistance, an introduction was given regarding the importance of washing hands with soap during this endemic period of COVID-19. Many PKK mothers do not understand the importance of using soap and prefer to use hand sanitizers which they feel are practical to carry anywhere. The manufacturing process is simple so that in the future PKK mothers can apply it themselves at home and it can become a platform for new businesses to develop. In addition, the traveling paper soap product that has been made can be used to tackle the problem of COVID-19 transmission during this endemic period. PKK mothers' understanding of the importance of using soap has increased after this service and PKK mothers have gained skills in making Traveling Paper Soap products.